2018
DOI: 10.22478/ufpb.1981-1268.2018v12n1.30719
|View full text |Cite
|
Sign up to set email alerts
|

Solo, topografia, mortalidade e recrutamento de árvores na floresta tropical decidual

Abstract: reSumo -Muitos são os fatores que podem aumentar ou diminuir a intensidade da dinâmica nas florestas tropicais. Com certeza o clima pode ser considerado fator determinante para as taxas de mortalidade e recrutamento de árvores nestas florestas. Entretanto, a topografia e o tipo de solo também são fatores que sinergicamente influenciam a distribuição e composição das espécies arbóreas, consequentemente alterando as taxas de dinâmica, pois algumas espécies são mais sensíveis às mudanças no ambiente. O objetivo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…However, species from moist soils were also observed, such as Alibertia edulis and Protium heptaphyllum. Even small changes in the water regime can induce changes in vegetation structure (Gusson, Vale, Araújo and Schiavini, 2012;Vale et al, 2013a) and the dam clearly favors water-associated species, such as those observed in other dams (Vale et al, 2013a). Some recent studies have shown that richness can increase over time, due to the establishment of moisture-associated associated species in sectors near the lakeshore created by the Groups 1(white), and 2 (small squares) consist of cerrado species, G3 (light gray), G4 (dark gray), and G5 (black) consist of forest species.…”
Section: Discussionmentioning
confidence: 99%
“…However, species from moist soils were also observed, such as Alibertia edulis and Protium heptaphyllum. Even small changes in the water regime can induce changes in vegetation structure (Gusson, Vale, Araújo and Schiavini, 2012;Vale et al, 2013a) and the dam clearly favors water-associated species, such as those observed in other dams (Vale et al, 2013a). Some recent studies have shown that richness can increase over time, due to the establishment of moisture-associated associated species in sectors near the lakeshore created by the Groups 1(white), and 2 (small squares) consist of cerrado species, G3 (light gray), G4 (dark gray), and G5 (black) consist of forest species.…”
Section: Discussionmentioning
confidence: 99%